(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the formation of the statehood of the Khorezmshahs, which operated in the 11th-13th centuries, their governance system, military-administrative structure, and foreign policy strategy. The study is based on medieval sources such as Juvayni, Rashid al-Din, and Ibn al-Athir, alongside modern historiography. The findings indicate that the Khwarazmshah state was a centralized monarchy with significant territorial expansion. However, internal political tensions and the Mongol invasion led to its decline. The article highlights the importance of Khwarazmshah statehood in Central Asian political history.